Study of rainfall-runoff relationship using hydrologic modeling system (HEC-HMS) for Lipis River - Nur Sharifah Ayu, Salim (2015)
In this study, Hydrologic Engineering Center – Hydrologic Modeling System (HEC-HMS) is used to determine the rainfall-runoff relationship of Lipis River, Pahang. HEC-HMS is software for use in analyzing, planning, and simulating the process of rainfall and runoff. HEC-HMS 4.0 is used in this study to simulate discharge for Lipis River. This study uses rainfall data and stream flow data from January 2008 to December 2014. The data needed is from eleven rainfall stations and one stream flow station in Lipis River catchment area. The analysis result of the data is depends on the parameter used in HEC-HMS. The parameters include time of concentration, storage coefficient, and lag time. The results of simulation can be generated in form of hydrograph, summary table, and time series table. Correlation coefficient, R2 is used to show the relationship of the simulated flow and the observed flow. If the correlation coefficient is close to 1.0, it would indicate that the variables are positively linear related. During evaluation of model, the best value of correlation coefficient is 0.7943 which nearly to 1.0. It shows that the simulated models were fit with the observed data and proves that the HEC-HMS is suitable to predict and analyze rainfallrunoff relationship in Lipis River.